"It Was Definitely Very Different": An evaluation of palliative care teaching to medical students using a mixed methods approach. Issue 1 (March 2015) - Brand, Alison H.; Harrison, Amanda; Kumar, Koshila
Given our ageing population and the increase in chronic disease, palliative care will become an increasingly important part of doctors' workloads, with implications for palliative care education. This study used a mixed methods strategy to evaluate second-year medical students' learning outcomes and experiences within a palliative care education program. Analysis of pre- and post-test scores showed a significant improvement in students' attitudinal scores, but no change in knowledge as measured by multiple-choice questions. Analysis of qualitative data revealed that students' learning experience was marked by a lack of clear learning objectives and experiential learning opportunities. Students also reported divergent reactions to death and dying and noted that palliative care was different from other areas of clinical medicine. This study revealed that palliative care teaching results in improved attitudes toward palliative care, reflecting the holistic and patient-focused nature of the palliative care curriculum.